Interactions of a short hyaluronan chain with a phospholipid membrane - Bełdowski, Piotr; Yuvan, Steven; Dėdinaitė, Andra; Claesson, Per M.; Pöschel, Thorsten (Colloids and Surfaces B: Biointerfaces, 2019)
Hyaluronic acid and phospholipids are two components that are present in the synovial fluid, and both are implicated as important facilitators of joint lubrication. In this work we aim to clarify how hyaluronic acid interacts with a phospholipid bilayer through their molecular interactions at the bilayer surface. To this end we performed molecular dynamics simulations of one hyaluronic acid molecule at a phospholipid bilayer in aqueous solution. The simulations were carried out for two aqueous solutions of equal concentrations, containing either NaCl or CaCl2. We analyzed hydrogen bonds, hydrophobic contacts and cation mediated bridges to clarify how hyaluoronic acid binds to a phospholipid bilayer. The analysis shows that calcium ions promote longer lasting bonds between the species as they create calcium ion bridges between the carboxylate group of hyaluronic acid and the phosphate group of the phospholipid. This type of additional bonding does not significantly influence the total number of contact created, but rather stabilizes the contact. The presented results can facilitate understanding of the role of hyaluronic acid and phospholipid interactions in terms of lubrication of articular cartilage.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Hyaluronic acid; Hydrogen bonds; Molecular dynamics simulations; Phospholipids